2002
DOI: 10.1071/ah020140
|View full text |Cite
|
Sign up to set email alerts
|

Subacute care and rehabilitation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The issue of selection criteria for other 'subacute' care is less clear than for rehabilitation, probably because definitions of what constitutes subacute care vary [18]. …”
Section: Resultsmentioning
confidence: 99%
“…The issue of selection criteria for other 'subacute' care is less clear than for rehabilitation, probably because definitions of what constitutes subacute care vary [18]. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a meta-analysis by Bhogal et al (2003) revealed that studies reporting significant treatment effects provided on average 8.8 hours of therapy per week for 11.2 weeks, while studies which revealed non-significant effects on language, involved treatments that were on average 2 hours week for 22.9 weeks. Despite this evidence, current service delivery models for aphasia within subacute facilities, (being goal based, time limited inpatient or outpatient healthcare facilities for conditions of moderate or low acuity Gray, 2002;Levenson, 2000) continue to remain non intensive and use predominately one-on-one individual SLP therapy. Modifying this traditional model to increase therapy intensity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the US report in 1997 that sub-acute care requires coordinated services of an interdisciplinary team, including physicians, nurses, and other relevant professionals who are knowledgeable and trained to assess and managed these specific conditions and perform necessary procedures [24]. Participants' suggestions also echoed to the Australia report in 2002 and study by Gray that other than the multidisciplinary rehabilitation, the selection criteria for sub-acute care (e.g., alternative to acute care or supplementary) should be flexible, probably because the components vary in different practice setting [15,25]. The general concept and components of sub-acute care, such as rehabilitation element, multidisciplinary, referral mechanism, etc.…”
Section: Discussionmentioning
confidence: 95%